Analisis Potensi Wisata Olahraga Trail Run di Gunung Pangradinan Kabupaten Bandung Jawa Barat - Muhamad Rofiq Munabil; Rizal Ahmad Fauzi; Adang Sudrazat (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to analyze the potential and development of the Tourism Trail Run sport destination in the Mount Pangradinan area, Bandung Regency, West Java based on the MSP+DM (Marketability, Sustainability, Participatory, Disaster Mitigation) framework. Using a qualitative case study method with a purposive sampling technique, this study involved 4 main informants consisting of management, athletes/visitors, and government representatives (KONI and DISPORA). Data were collected through observation, documentation, and semi-structured interviews, which were then systematically analyzed using NVivo 12 software through open coding, axial coding, and determining the main themes. The results show that Mount Pangradinan has strong strategic potential, characterized by the unique characteristics of the natural track with a 3-in-1 model (competition, recreation, culture), environmental commitment through visitor quotas (carrying capacity), a positive multiplier effect on improving the economy of local MSMEs, and the readiness of risk mitigation management that is responsive to the threat of natural and non-natural crises in the field. Keywords: Sport Tourism, Trail Run